Determine the Groundwater Recharge Zones in Erbil Basin - Mustafa, Jwan Sabah; Mawlood, Dana Khider (Transactions on Engineering and Computing Sciences, 2024)
The identification and delineation of recharge zones are critical components in sustainable groundwater management. This study focuses on determining the recharge zones within the Erbil Basin, employing a combination of field investigations, hydrogeological assessments, and geospatial analyses using Groundwater Modeling system (GMS) software with the aid of Geographic information System (GIS). The study uses the historical and field observed geological formations data to evaluate the 3D visualization of unconfined, confined and semi-confined aquifer types within Erbil Basin in order to determine the Recharge area. The aim is to provide valuable insights into the spatial distribution and characteristics of areas where groundwater recharge predominantly occurs. The outcomes of this research contribute to a comprehensive understanding of recharge dynamics in the Erbil Basin. The delineation of recharge zones provides essential information for sustainable groundwater management, aiding in the development of effective land use planning and conservation strategies. The results of this study reveal a decline in groundwater levels within the Erbil basin over the period from 2004 to 2023. were 86.2 meters in the Kasnazan well and 125.86 meters in the Mala Omer well, both located within recharge zones of the Erbil groundwater basin. The findings will be valuable for local authorities, policymakers, and water resource managers, offering a basis for informed decision-making to ensure the long-term viability of groundwater resources in the Erbil Basin. The study emphasizes the importance of integrating multidisciplinary approaches to accurately identify and protect the crucial zones responsible for replenishing the groundwater system.